Pengaruh Media Lapbook terhadap Kemampuan Mengenal Huruf pada Anak Usia 4-5 Tahun - Sumah, Regita Cahyani Maulida; Ardini, Pupung Puspa; Sutisna, Icam (Efektor, 2025)
This study is motivated by the low ability of children in recognizing letters, as well as the lack of utilization of learning media used to support the process. The purpose of this study is to determine the effect of using lapbook media on the ability to recognize letters in children aged 4-5 years at Kamboja Kindergarten, Central City District, Gorontalo City. This study applied saturated sampling technique which involved all group A as many as 19 people. The approach used was quantitative research and experimental method with one group pretest-posttest design. Data collection was done through performance tests. The results of hypothesis testing that the significance value of 0.000 < α = 0.05 and the value of t count = 15.650 and t table = 1.729 then H0 is rejected and H1 is accepted. It can be concluded that there is an effect of lapbook media on the ability to recognize letters in children 4-5 years at Kamboja Kindergarten